PERAN KOMUNIKASI INTERPERSONAL PRAMUWISATA BERBAHASA INGGRIS DISCOVA DALAM MENINGKATKAN KUALITAS HUBUNGAN DAN KEPUASAN WISATAWAN - Ni Luh Dea Enjelita; Ni Putu Evi Wijayanti; I Gede Ngurah Primanda S Rahadiarta (Politeknik Pariwisata Bali, 2025)
This study is motivated by the crucial role of interpersonal communication in shaping a satisfying tourism experience. Amid the increasing number of international tourists visiting Bali, English-speaking tour guides play a key role in establishing high-quality interactions. The objective of this research is to analyze the forms of interpersonal communication used by Discova tour guides, the factors influencing its effectiveness, and its contribution to relationship quality and tourist satisfaction. A mixed-method approach was applied, with descriptive qualitative methods as the main framework, supported by quantitative methods. Data were collected through in-depth interviews with 15 tour guides and questionnaires distributed to 100 tourists who had used Discova’s services. Qualitative data were analyzed using NVivo, while quantitative data were processed using SPSS with validity and reliability testing. The results indicate that interpersonal communication—including openness, empathy, supportiveness, positiveness, and equality—significantly enhances the quality of relationships between tour guides and tourists. Post-tour communication via social media further strengthens emotional bonds. These findings demonstrate that effective interpersonal communication plays a vital role in fostering tourist satisfaction and loyalty toward Discova’s services.